A model to diversify the Algerian economy outside the dependence of the hydrocarbons sector : A Forward looking Vision - LOUCIF, Amar; LABED, Lazhar (Journal of Human Sciences, 2019)
This study aims to investigate the success and efficiency of the economic diversification model adopted in Algeria since 2016, and the most important challenges facing it, especially with the low prices of fuel in international markets in recent years. Herfindal-Hirschmann’s coefficient of economic diversification was derived from the development of two variable structures: Gross domestic product and exports during the period (2012-2016). The study showed that there was no diversification in the structure of both gross domestic product and exports during the period (2012-2016). On the other hand, the economic diversification model remains a forward-looking vision and an opportunity for the Algerian economy to eliminate the risks posed by the almost total dependence on the hydrocarbon sector.